The old boat - Pumphrey, Jarrett; Pumphrey, Jerome (Norton Young Readers, an imprint of W. W. Norton and Company, 2021)
"Off a small island, a boy and his grandfather set sail in their beloved fishing boat. They ride the waves, catching wants and wishes and seeing the wonders of the ocean. But soon the boy is sailing the boat himself, drifting further from shore as the waters grow muddied and turbulent. When a storm washes him ashore, he sees home in a new light. He decides to turn the tides of his fortune, cleaning the island's waters and creating a new life with a family to call his own"--